2004
DOI: 10.1074/jbc.c400333200
|View full text |Cite
|
Sign up to set email alerts
|

p150Glued, Dynein, and Microtubules Are Specifically Required for Activation of MKK3/6 and p38 MAPKs

Abstract: To look for regulators of the mitogen-activated protein kinase (MAPK) kinase 6 (MKK6), a yeast two-hybrid screen was initiated using MKK6 as bait. p150Glued dynactin, a key component of the cytoplasmic dynein-dynactin motor complex, was found to specifically interact with MKK6 and its close homologue MKK3. Silencing of p150Glued expression by small interference RNA reduced the stimulus-induced phosphorylation of MKK3/6 and p38 MAPKs. The similar adverse effect was also seen when the cytoplasmic dynein motor wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 20 publications
1
27
1
Order By: Relevance
“…A potential unifying model is that NF-B may undergo active transport using dynein following stimulation, while shuttling may be diffusion-mediated. If shuttling is diffusionmediated, enhancement of the process by dynactin disruption could be consistent with emerging roles for dynactin in nonmotile processes such as tethering of signaling molecules (15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…A potential unifying model is that NF-B may undergo active transport using dynein following stimulation, while shuttling may be diffusion-mediated. If shuttling is diffusionmediated, enhancement of the process by dynactin disruption could be consistent with emerging roles for dynactin in nonmotile processes such as tethering of signaling molecules (15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 56%
“…Dynactin can regulate the processivity of multiple molecular motors and dynactin disruption can disable both anterograde and retrograde trafficking (11,12); in addition, dynactin may act as a scaffold to dock anchoring or signaling proteins independently of its role in cellular transport (15)(16)(17)(18)(19). To directly assess the role of cytoplasmic dynein in the NF-B response to diverse activating stimuli in multiple cell types, we designed shRNAs against the heavy chain of dynein for both mouse and human species.…”
Section: Loss Of Endogenous Dynein Function Inhibits Stimulus-inducedmentioning
confidence: 99%
See 1 more Smart Citation
“…Dyneins are microtubuleassociated motor protein complexes and has been reported that in vivo it is necessary for the activation of MAPK (mitogen-activated protein kinase) kinase3/6 and p38 (Cheung et al, 2004). The p38-MAPK pathway plays important roles in the regulation of several biological progresses including cell survival, differentiation, migration (Cuenda et al, 2007;Cuadrado et al, 2010), immune and inflammatory responses (Han et al, 1994;Lee et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…B78H1 cells were maintained in Dulbecco's modified Eagle's medium (DMEM) with 10% fetal bovine serum (FBS). The construction and packaging of the equine macrophage cDNA library into the pFB murine retrovirus (7,48) were described earlier, and this library was kindly provided by Ron Montelaro (University of Pittsburgh). The EHV-1 lacZ reporter virus, L11⌬gI⌬gE was described previously (16).…”
Section: Methodsmentioning
confidence: 99%